EVOLUŢIA ECONOMIEI NAŢIONALE DUPĂ DECLARAREA INDEPENDENŢEI REPUBLICII MOLDOVA - Certan, Simion; Certan, Ion (CEP USM, 2011)
The Declaration of independence practically broke the centralized economic system and re-oriented the national economy towards one based on free market relationship, reform that convert public property into private, ensuring of a balance within the economy’s braches, adjusting them to local specifics, etc. In this article the authors present an impartial study of the national economy evolution through the prisms of reforms effects, analyzed the impact of public-private conversion on resources and their availability.
Keywords: economia naţională; evoluția economiei